2022
DOI: 10.3389/fphy.2022.1068838
|View full text |Cite
|
Sign up to set email alerts
|

A review of piezoelectric metamaterials for underwater equipment

Abstract: As an important tool for monitoring the marine environment, safeguarding maritime rights and interests and building a smart ocean, underwater equipment has developed rapidly in recent years. Due to the problems of seawater corrosion, excessive deep-sea static pressure and noise interference in the marine environment and economy, the applicability of manufacturing materials must be considered at the beginning of the design of underwater equipment. Piezoelectric metamaterial is widely used in underwater equipmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Lattice materials with engineered properties (piezoelectric and electromagnetic) are further used in microelectromechanical systems and sensors due to their tunable mechanical performance and flexibility. [199][200][201] As such, the piezoelectric properties allow the conversion of energy between mechanical and electrical domain, which opens the doors for applications in actuators, sensors, and ultrasound imaging. [202] Several designs were proposed to enhance the piezoelectric and electromagnetic properties of such lattice materials.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lattice materials with engineered properties (piezoelectric and electromagnetic) are further used in microelectromechanical systems and sensors due to their tunable mechanical performance and flexibility. [199][200][201] As such, the piezoelectric properties allow the conversion of energy between mechanical and electrical domain, which opens the doors for applications in actuators, sensors, and ultrasound imaging. [202] Several designs were proposed to enhance the piezoelectric and electromagnetic properties of such lattice materials.…”
Section: Applicationsmentioning
confidence: 99%
“…[202] Several designs were proposed to enhance the piezoelectric and electromagnetic properties of such lattice materials. [199,200,203,204] For instance, Khan et al [205] designed a piezoelectric honeycomb lattice material with zero and negative Poisson ratios. The results revealed that such structures could be further developed with adjustable electromechanical properties, yielding lightweight devices for nextgeneration sensors and actuators.…”
Section: Applicationsmentioning
confidence: 99%
“…Ultrasonic transducer is an electronic device that converts ultrasonic waves into electrical energy and vice versa. According to the working principle, ultrasonic transducers can be divided into electric field types, like capacitive and piezoelectric, and magnetic field types, such as magnetostrictive transducers [1][2][3][4][5]. The earliest notable ultrasonic transducer was a sandwich transducer designed by Langevin in 1917 [6].…”
Section: Introductionmentioning
confidence: 99%
“…By altering the geometry of the microstructure some mechanical properties like stiffness or density can be tailored for specific applications but most importantly, materials with unconventional characteristics like negative effective Poisson's ratio, so-called auxetic materials, can be obtained (Alderson and Alderson, 2007;Carneiro et al, 2013). The exceptional ability of auxetic materials to contract in transverse directions under compressive load opens up a range of possibilities for energy harvesting (Zhao et al, 2022). Auxetic cellular honeycomb (HC) structures are the most popular auxetic metamaterials, widely studied in the literature due to their relatively simple geometry (Iyer and Venkatesh, 2011;Iyer et al, 2015;Khan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%